Can the Efficiency of Islamic Banks in Indonesia Improve Their Competitiveness? - Muhammad Iqbal; Dwi Yanti Yunianita (UIN Siber Syekh Nurjati Cirebon, 2020)
The development of Islamic banks today has contributed to the emergence of increasingly competitive competition between Islamic banks. Efficiency performance is believed to be a major factor in driving competitiveness among Islamic banks. This study aims to analyze the efficiency performance of Islamic banks in Indonesia and their effect on competitiveness. The sample used was 11 Islamic banks in Indonesia. The data used in this study were obtained from annual financial reports published from the OJK website and each bank during the period of 2012 - 2017. The approach used to measure efficiency performance uses the Data Envelopment Analysis (DEA) method, while the data analysis method uses One Way ANOVA and panel data regression. The results of measuring the efficiency performance of Islamic banks in Indonesia are still quite efficient, although during the study period several banks experienced a decrease in efficiency which resulted in differences in efficiency of performance among Islamic banks. Changes in efficiency performance do not have an impact on the competitiveness of Islamic banks themselves.